Efektivitas Pelayanan Jaminan Kesehatan Berbasis Elektronik pada Kantor Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan Kabupaten Karawang - Adila Alanisagita Pusung; Hanny Purnamasari (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2024)
This study aims to evaluate the effectiveness of electronic services provided by BPJS Kesehatan in Karawang Regency. The electronic services are expected to facilitate public access to services such as membership registration, health facility transfers, and others online, without the need to visit the BPJS Kesehatan office in Karawang Regency. However, the use of these electronic services remains limited among the people of Karawang Regency. This study employs a qualitative approach to gain an in-depth understanding of the issues surrounding the effectiveness of BPJS Kesehatan’s electronic services in Karawang Regency. Data collection and analysis refer to Effectiveness Theory. The study utilizes data from BPJS Kesehatan staff in Karawang Regency and BPJS participants in the area, with data gathered through observation, interviews, documentation, and literature review. The findings indicate that the electronic services provided by BPJS Kesehatan in Karawang Regency are not yet effective. The outreach efforts have not optimally increased public understanding, are not well-targeted, and there are system issues that slow down service delivery. The goal of electronic services—to provide easy, fast, and equitable access—has not yet been achieved, meaning the expected changes in the community have not materialized. To enhance service effectiveness, it is recommended to broaden well-targeted outreach efforts, conduct regular system maintenance, and collaborate with relevant agencies in Karawang Regency and the community so that the goals of electronic services can be achieved and bring about positive change for the public.